Deep‐Time Paleoclimate Proxies - Francis A. Macdonald (AGU Advances, 2020)
Abstract Pre‐Cenozoic climate (>66 million years ago) has been reconstructed with climate sensitive sedimentary deposits. However, sedimentary records are inherently local and can be affected by topography and oceanic and atmospheric currents. Additionally, in tectonically active environments, the interpretation of glacigenic rocks can be ambiguous. Temperature and CO2 proxies complement the record of climate sensitive sedimentary rocks. With samples that have been carefully screened for post‐depositional alteration, carbonate clumped isotope thermometry has produced ocean temperature estimates that are consistent with the sedimentary record and CO2 proxy data. Although there are many challenges for quantitative temperature reconstructions through Earth history, maximum temperature estimates are now being extracted across the onset of Cryogenian (720–635 million years ago) snowball Earth glaciations that follow the expected cooling trend.